THE INFLUENCE OF READING HABITSAND READING STRATEGIES ON STUDENTS’ READING COMPREHENSION ATJUNIOR HIGH SCHOOL 1 IN THE DISTRICT OFBENAI-KUANSING - Nurmania Fitri (Journal of Education and Teaching, 2021)
The purpose of this study was to the influence reading habits and reading strategies on students reading comprehension at junior high school 1 in the district Benai-Kuansing.There were three questions contained in this study.Firstly,Is there any significant  influence of reading habit on students’ reading comprehension in junior high school 1  Benai.Secondly, Is there any significant  influence of reading strategies on students’ reading comprehension in junior high school 1  Benai.Thirdly, Is there any significant  influence of reading habit and reading strategies on students’ reading comprehension in junior high school 1  Benai.This study used quantitative explanatory research. The subjects in this study are 70 students of the second grade students. Data collection techniques in this study used questionnaires and tests. The questionnaires in this study related to students' reading habits and students' reading strategies, while the tests related to student reading comprehension. The data obtained were analyzed using descriptive statistics, classic assumption tests, multiple regression tests and hypothesis testing.The results of this study indicate that, student reading habits (X1) have significant results of 0,685. Student reading strategies (X2) have significant results of 0.379. And student reading comprehension (Y) has a significance result of 0.818. Therefore, the researcher concludes that there is a positive and significant contribution of student reading habits and student reading strategies on student reading comprehension. Keywords:Reading Habit, Reading Strategies, Reading Comprehension.